2014
DOI: 10.18632/oncotarget.2003
|View full text |Cite
|
Sign up to set email alerts
|

HGF/MET-directed therapeutics in gastroesophageal cancer: a review of clinical and biomarker development

Abstract: Aberrant activation of the HGF/MET signaling axis has been strongly implicated in the malignant transformation and progression of gastroesophageal cancer (GEC). MET receptor overexpression in tumor samples from GEC patients has been consistently correlated with an aggressive metastatic phenotype and poor prognosis. In preclinical GEC models, abrogation of HGF/MET signaling has been shown to induce tumor regression as well as inhibition of metastatic dissemination. Promising clinical results in patient subsets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 91 publications
0
60
0
Order By: Relevance
“…Complete resection of localized tumors is the mainstay of treatment, but patients newly diagnosed with gastric cancer tend to present with advanced and often incurable disease (42). The MET RTK is frequently dysregulated and strongly implicated in the malignant transformation and progression of this disease (43).…”
Section: Discussionmentioning
confidence: 99%
“…Complete resection of localized tumors is the mainstay of treatment, but patients newly diagnosed with gastric cancer tend to present with advanced and often incurable disease (42). The MET RTK is frequently dysregulated and strongly implicated in the malignant transformation and progression of this disease (43).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that inactivating HGF using antibodies and/or inhibiting the HGF/c-Met signaling pathway may be a potential therapeutic approach for regulating the angiogenesis and metastasis of tumorigenic tissues (Grugan et al, 2010). There are promising targeted therapy strategies that have demonstrated favorable results in both completed and ongoing preclinical studies (Hack et al, 2014). The results of these studies reveal the need for biomarkers that are not only used for diagnosis and prognosis, but also for determining patients who are more prone to benefit from targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to qPCR, most studies that performed the IHQ methodology do not have a consensus on the score criteria to test c-Met [15]. Furthermore, this technique has several variables involved, such as: the use of heterogeneous samples, with different tissue sections and sizes; variation between observers; a large range of primary and secondary antibodies and their particularities; staining protocols; methods used for the score; differences in the samples' processing or handling; and storage conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this technique has several variables involved, such as: the use of heterogeneous samples, with different tissue sections and sizes; variation between observers; a large range of primary and secondary antibodies and their particularities; staining protocols; methods used for the score; differences in the samples' processing or handling; and storage conditions. Besides, the used IHC reagents often vary their specificity and sensitivity [15]. All these factors have implications for the use of c-Met and its ligand in the IHC method, which made us to opt for the qPCR technique for the pilot study, instead of using the IHQ that was also an option, considering our small sampling and poor amount of tissue in the paraffin blocks to standardize more than one procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation